Email Analysis in Fraud Investigation: Digital Forensic and Network Analysis Approach - Wishnu Agung Baroto (Asia Pacific Fraud Journal, 2021)
Email is an imperative method of communication that is changing the way people share their data and information. It provides effective and efficient communication, especially in business, convenience, and easy access and replication. Those electronic data should be considered by a fraud investigator to comprehend the investigation. Email can be divided into two parts: the head of the email and the email body. The head of the email is metadata that consists of unstructured data, and the body and its attachment consist of semi-structured data. The email data usually comes in large volumes and ranges of types. Therefore, a manual investigation of an email should be avoided. This paper uses the Design Science Research Methodology to discover the most profound framework in an email fraud investigation. Using email metadata and email body, this research performs a digital forensic framework: preparation, gathering, processing, and presentation, combines with social network analysis to be applicable in the investigation. The result shows that digital forensics process, network analysis, data visualization provides a more valuable and comprehensive insight into email analysis.